Sosialisasi Dan Pelatihan Cara Beternak Kelinci Bagi Peternak Kelinci Di Kabupaten Soppeng - Utami, Sri Wira; Sonjaya, Herry; Tullah, Muh. Firdaus; Irwan, Irwan; Aksan, Muhammad; R, Muh. Faisal Rahmat (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Rabbits are livestock that are easy to breed in Indonesia. Rabbits are one of the sources of livelihood for the "Mandiri" rabbit farming group under the guidance of TP PKK, Salokaraja Village, Lalabata District, Soppeng Regency. The rabbit farming business is used as income for business sustainability and development, as well as to meet daily needs. However, this potential is hampered by the large number of deaths and the decline in the quality of adult rabbit production. The cause of this problem is the farmer's low knowledge of rabbit diseases and the success of pregnancy after mating. The methods used in this activity are counseling, pre-test, and post-test, mentoring and training for group members and final evaluation. The results of the activity are that the rabbit farming group is still developing a business based on raising rabbits as pets or ornamental rabbits for sale and has not yet made meat rabbits for sale for consumption and there is no meat processing for processed products. The main problem that is also the topic of counseling and training is health problems such as skin disease (scabies) and sometimes mothers who have been mated also do not give birth, after checking it turns out that the mating was not successful or failed to get pregnant. There is still a lack of education about the health benefits of consuming rabbit meat compared to other livestock, so interest in raising meat rabbits for consumption and as processed products is still low. So, through this outreach it can be a forum for education for breeders who do not yet know the advantages and benefits of rabbit farming. So that this rabbit farm can become a business unit that is able to expand employment opportunities for the community, especially breeders, towards potential new entrepreneurs.